PENGEMBANGAN E-MODUL MENGGUNAKAN HEYZINE PADA MATA PELAJARAN INFORMATIKA EKSPRESI DAN OPERASI LOGIKA FASE D KELAS IX DI SMP NEGERI 22 SAMARINDA - Yudha Saputra, Galih; Dwi Rizky Kurniawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop an e-module using Heyzine on Informatics subject, specifically on logical expressions and operations for grade IX students. This research uses a Research and Development (R&D) approach with the 4D model (Define, Design, Develop, Disseminate). The subjects of this study were students of class IX F at SMP Negeri 22 Samarinda. Data were collected through interviews, observations, and questionnaires. The results showed that the developed e-module was categorized as highly feasible based on expert validation and student responses. The material expert validation obtained a score of 73 (very feasible), media expert validation obtained an average score of 68.67 (very feasible), and student trial results obtained a score of 61.39 (very feasible). Therefore, the developed e-module is suitable to be used as an interactive learning material to improve students’ understanding and learning motivation.